A Decade of Electrical Injuries: An Epidemiological Analysis of Emergency Department Data - Yasemin Adalı; İbrahim Türkçüer; Yasemin Berberoğlu; Veli Kaan Aydın; Atakan Yılmaz; Mert Özen; Murat Seyit; Alten Oskay; Aylin Köseler (Emergency Medicine International)
Conclusion: Biochemical evidence of myocardial injury was observed even in low-voltage exposures, raising concerns about the safety of early discharge based solely on clinical presentation and ECG findings. Prospective studies are needed to refine risk assessment strategies in electrical injury cases.